PERBANDINGAN PREFERENSI MASYARAKAT TERHADAP OBAT TRADISIONAL DAN OBAT SINTETIK DI APOTEK QUALITY KOTA BEKASI TAHUN 2019 - yanti, dharma; Nurhayati, Nunung (STIKes Medistra Indonesia, 2022)
Drugs based on their active ingredients are divided into two, namely traditional drugs (derived from natural ingredients) and synthetic drugs (derived from chemicals). This study aims to compare the factors that influence people's preferences between choosing traditional and synthetic drugs at Apotek Quality, Jatibening in the city of Bekasi. The design of this research is non-experimental observation with a comparative approach. The research was conducted in Decembre 2019 for 3 weeks at Apotek Quality, Jatibening. The population in this study were all people who visited and or bought drugs at the Quality Pharmacy, Jatibening who were adults (> 18 years). The sampling technique used is the Incidental Sampling technique. Collecting data using direct interviews with the help of a questionnaire instrument, the data is then processed with Microsoft Excel. The results of this study indicate that the preference for traditional medicine is 55% and for synthetic medicine is 45%. Significant preference factors for traditional medicine are economic factors and psychological factors, while and synthetic drugs are dominated by psychological factors, this conclusion is drawn from a Likert scale questionnaire about the use of traditional and modern medicines. Characteristics of respondents related to drug preferences analyzed using the Chi Square method are: age, complaints of illness, occupation, sources of information about drugs and economic status. Characteristics of respondents that are not related to drug preference are: ethnicity, gender, marital status and education level